2020
DOI: 10.3390/md18080429
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Physicochemical Characteristics and Macrophage Immunostimulatory Activities of Polysaccharides from Chlamys farreri

Abstract: To address the structure–activity relationship of Chlamys farreri polysaccharides on their immunostimulatory efficacy, two polysaccharides (CFP-1 and CFP-2) were extracted from Chlamys farreri by hot water extraction, and separated through column chromatography. The isolated CFPs were chemically analyzed to clarify their physicochemical characteristics and cultured with murine macrophage RAW264.7 cells, in order to evaluate their immunostimulatory efficacy. Despite the fact that both CFP-1 and CFP-2 were mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
2
0
1
Order By: Relevance
“…Биологическая активность полисахаридов морских макрофитов зависит от таких факторов, как молекулярная масса, степень сульфатирования, плотность заряда, структурные и конформационные характеристики [84,85]. При этом одной из важнейших физико-химических характеристик макрофитных полисахаридов является их растворимость в воде [86]. Структуру полисахаридов можно модифицировать для получения синтетических производных с желаемыми характеристиками, что может значительно повышать их биологическую активность [83].…”
Section: получают его из высушенных корней куркумыunclassified
“…Биологическая активность полисахаридов морских макрофитов зависит от таких факторов, как молекулярная масса, степень сульфатирования, плотность заряда, структурные и конформационные характеристики [84,85]. При этом одной из важнейших физико-химических характеристик макрофитных полисахаридов является их растворимость в воде [86]. Структуру полисахаридов можно модифицировать для получения синтетических производных с желаемыми характеристиками, что может значительно повышать их биологическую активность [83].…”
Section: получают его из высушенных корней куркумыunclassified
“…Scallop visceral mass and mantle are the main byproducts during scallop processing which are considered low value and usually discarded as waste [ 1 ]. However, the scallop visceral mass and mantle have a high content of protein and contain plenty of bioactive substances with anti-virus, anti-tumor and immunostimulatory activities [ 2 , 3 ]. It was reported that scallop muscle contained tropomyosin and actin [ 4 ], and functional products were extracted from the scallop mantle, such as the protein hydrolysate exhibiting abilities to reduce hydroxyl and DPPH radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfated polysaccharides from Codium fragile (green sea fingers) enhance the cytotoxicity of natural killer cells toward HeLa cells by increasing the release of cytokines and cytotoxic granules [ 8 ]. Polysaccharides from Chlamys farreri (marine bivalve mollusc) and sea cucumber viscera promote phagocytosis and increase cytokine production in macrophages [ 9 , 10 ]. The water-soluble polysaccharides from Cuminum cyminum activate RAW264.7 cells and NK-92 cells, causing them to produce cytokines [ 11 ].…”
Section: Introductionmentioning
confidence: 99%